Canine nail bed keratoacanthoma diagnosed by immunohistochemical analysis - Yoo, Chang-Bum (Can Vet J, 2015)
A 10-year-old, Shih Tzu dog was presented with an enlarged, curled 2nd nail in the left forelimb. Digital amputation was performed and the mass was diagnosed as a nail bed keratoacanthoma (infundibular keratinizing acanthoma) histopathologically. There was no recurrence postoperatively. This is the first case report of a canine nail bed keratoacanthoma diagnosed by histologic and immunohistochemical examination including Ki-67 and p53 expression.